Enhancing Learning Processes and Outcomes in IPAS (Science, Environment, and Social Studies) through Problem-Based Learning for Elementary School Students - Nabila Nabila; Sundahry Sundahry; Nurlev Avana (JIE (Journal of Islamic Education), 2025)
This study was motivated by the problem of low student engagement and limited achievement levels in Science, Environment, and Social Studies (IPAS) learning. To address this issue, the research aims to enhance learning processes and outcomes by implementing Problem-Based Learning (PBL) in a fourth-grade elementary classroom. He used a Classroom Action Research (CAR) design with the Kemmis and Taggart model in two cycles, consisting of involving planning, action, observation, and reflection. Data were collected through observations, tests, and questionnaires with 10 fourth-grade students at SDN 86/II Timbolasi. Data were analysed using qualitative descriptive techniques for observations and questionnaires. Researchers also conducted quantitative data analysis using descriptive statistics. The study revealed notable improvements from Cycle I to Cycle II, demonstrating the effectiveness of implementing Problem-Based Learning in enhancing teaching quality and student outcomes. Teacher performance increased significantly from 55% in Cycle I to 90% in Cycle II. Likewise, student engagement rose markedly, from 70% in Cycle I to 90% in Cycle II, with the latter categorised as "very good." These changes were then evaluated and reflected in the second cycle initiative planning, leading to instructional strategy refinement. The research was conducted with a small sample size in a single rural school, which may limit the generalizability of the findings. However, the results provide valuable guidance for integrating PBL with interactive media to improve student-centred learning. This study offers empirical evidence of PBL’s effectiveness in interdisciplinary elementary education within rural contexts, highlighting the role of facilitative teaching strategies and multimedia integration in fostering critical thinking, collaboration, and deeper understanding among young learners.